2021
DOI: 10.1016/j.bpj.2021.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the mechanism of octenidine and chlorhexidine on membranes: Does electrostatics matter?

Abstract: The increasing problem of antibiotic resistance in bacteria requires the development of new antimicrobial candidates. There are several well-known substances with commercial use, but their molecular mode of action is not fully understood. In this work, we focus on two commonly used antimicrobial agents from the detergent family-octenidine dichloride (OCT) and chlorhexidine digluconate (CHX). Both of them are reported to be agents selectively attacking the cell membrane through interaction inducing membrane dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 70 publications
5
29
0
1
Order By: Relevance
“…Levofloxacin [236][237][238], Clarithromycin [236], Isoniazid N -acylated derivatives [239], Rifampicin [234,240], Mangostin [241], Trimethoprim [242], Negamycin [243] Potential antibiotic Kanamycin A [133], nTZDpa and its derivatives [244], Cholic acid derived amphiphiles [245], γ-terpineol [246], Bithionol [247] Antimicrobial compound Chlorhexidine [248][249][250], Triclosan [251], Octenidine [250] Antiparasitic Praziquantel [252] Antiviral drugs Darunavir [253], Amantadine [254][255][256], Spiro[pyrrolidine-2,2 -adamantane] [254,255], 20,30-dideoxyadenosine (Didanosine) [242], Saffron [257] Antifungal drug Itraconazole, [184,186,187,258], Nystatin [259], Amphotericin B [260] Rheumatoid arthritis Lapatinib [213] Nonsteroidal antiinflammatory drugs, inhibitor of cyclooxygenase-1 and -2…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
“…Levofloxacin [236][237][238], Clarithromycin [236], Isoniazid N -acylated derivatives [239], Rifampicin [234,240], Mangostin [241], Trimethoprim [242], Negamycin [243] Potential antibiotic Kanamycin A [133], nTZDpa and its derivatives [244], Cholic acid derived amphiphiles [245], γ-terpineol [246], Bithionol [247] Antimicrobial compound Chlorhexidine [248][249][250], Triclosan [251], Octenidine [250] Antiparasitic Praziquantel [252] Antiviral drugs Darunavir [253], Amantadine [254][255][256], Spiro[pyrrolidine-2,2 -adamantane] [254,255], 20,30-dideoxyadenosine (Didanosine) [242], Saffron [257] Antifungal drug Itraconazole, [184,186,187,258], Nystatin [259], Amphotericin B [260] Rheumatoid arthritis Lapatinib [213] Nonsteroidal antiinflammatory drugs, inhibitor of cyclooxygenase-1 and -2…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
“…Finally, data from both geometry and a Hessian matrix were used for parametrisation of modelled particles and the force fields creation. This approach was successfully used beforehand to create force fields for various particles [18,50,51]. In Supporting Materials (SM) we have delivered the detailed base of modelled 250 particles (see Microsoft Excel datasheet) with optimised force fields (see included zip file).…”
Section: Parametrisationmentioning
confidence: 99%
“…As previously stated, Gemini molecules are well-known for their antimicrobial activity. It was considered by Epand et al [21] as well as shown in the OCT studies, that this effect is related to membrane disruption [18]. The effect of those Gemini molecules on the membrane properties was assessed to determine the properties that most likely correspond to the antimicrobial effect.…”
Section: Membrane Characterisationmentioning
confidence: 99%
See 2 more Smart Citations